Die sorgsame toesighoudingsplig van ‘n siviele tegnologie werkswinkel–onderwyser ter bevordering van leerderveiligheid - Oosthuizen, Josef Jacobus (North-West University, 2011)
The concept duty of care is defined as heedful, careful guarding, supervision of a minor, and/or overseeing. An obligation rests on teachers to scrupulously see to the safety (and also the well-being) of all learners entrusted to them. Hence teachers are responsible for the physical safety of learners and for creating a safe haven for them. The Civil Technology workshop teacher has an increased caring duty towards his learners due to the potential life-threatening circumstances and conditions that can prevail in his workshop compared to, for instance, the ordinary classroom environment. Furthermore, a specific legal duty rests on a person when he is placed in control of dangerous objects or machinery, seeing that he has to see to it that he ensures the safety of others through positive action. Internationally, the circular saw is statistically speaking seen to be the most dangerous woodwork machine in the Civil Technology workshop. Circular saws are responsible for more accidents than any other machine, and the most claims for damages against teachers and school managements also arise from it. Due to the underlying dangers inherent to circular saws and the presence thereof in Civil Technology workshops, it increases the risks attached to the caring supervision duty of the Civil Technology teacher to a great extent. Civil Technology workshop teachers are therefore confronted by unique challenges in their workshops. Hence it is essential that they be equipped with sufficient knowledge pertaining to educational law so as to make head against these challenges. Civil Technology workshop teachers should therefore not only be aware of all common law principles, relevant legislation and case law as applicable to workshops, but also be able to apply it in practice in the workshop environment. This practical application furthermore requires workshop teachers to be knowledgeable to be able to maintain workshop machinery in a safe working condition through regular upkeep and maintenance. An empirical investigation (n=38) was launched, based on a questionnaire filled in by all Civil Technology teachers and their heads of department North West where Civil Technology is presented as a choice subject at high schools. The aim of the empirical investigation was to determine: * what the level of Civil Technology workshop teachers' expertise and knowledge is regarding legal key issues concerning their caring supervising duty, and * to what extent effective safety management of woodwork machinery in Civil Technology workshops is applied. The empirical investigation found, amongst others, that: * The respondents do not have sufficient knowledge of the principles pertaining to educational law to apply it in the Civil Technology workshops of the study population practically. * Civil Technology workshop teachers and heads of department should have a high degree of expertise with a view to execute their duty of care. Poor educational law training can possibly be proffered as reason why their level of expertise cannot be seen to be sufficient in a case where an increased level of duty of car is required in potentially dangerous workshops. Following on above-mentioned findings, specific recommendations were made to all role-players involved that are involved in learner safety in Civil Technology workshops. These recommendations may possibly contribute to increased and more effective caring supervision in promoting learner safety.
Thesis (MEd (Education Law))--North-West University, Potchefstroom Campus, 2012
Keywords: Workshop; Woodshop; Teacher / Instructor; Shop safety; Learner safety; Injury; Negligence; Liability; Legal duty of care; Tort law; Industrial arts; Vocational studies; Circular saw accidents; Band saw; Nalatigheid; Sorgsame toesighouding; Werkswinkel; Opvoeder; Aanspreeklikheid; Deliktereg